PERAN LITERASI KEUANGAN DALAM MEMBENTUK PERILAKU FINANSIAL GENERASI MUDA: SEBUAH TINJAUAN SISTEMATIS - Dimas Putri Mega Pratesa; Adinda Yosa Novaretha (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2026)
Financial literacy is an individual's ability to understand, manage, and make the right decisions related to personal finances. In the modern era, the low level of financial literacy among the younger generation has become a global issue that has an impact on consumptive behavior, increased debt, and low readiness to face economic risks. This study aims to analyze the role of financial literacy in shaping wise financial behavior in the younger generation, as well as identify the factors that affect the level of financial literacy. The method used was a systematic literature review of 9 scientific articles published between 2020 - 2024 and obtained from various scientific databases. The results of the study show that financial literacy has a positive and significant effect on the financial behavior of the younger generation. Factors that support the improvement of financial literacy include formal education, family environment, financial self-efficacy, lifestyle control, and the use of digital technology. This research emphasizes that increasing financial literacy is a strategic step in shaping an economically resilient young generation. Synergy is needed between educational institutions, the government, and financial institutions in expanding access to digital-based financial education and sustainable financial literacy programs.